THE ROLE OF AI (ARTIFICIAL INTELLIGENCE) IN STUDENT LEARNING - Muhammadova Gavhar Fazliddin qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Artificial Intelligence (AI) has become one of the most influential forces shaping  modern  education.  By  providing  adaptive,  personalized,  and  data-driven learning experiences, AI enables students to reach their potential more efficiently. This paper examines the main roles of AI in student learning, focusing on its applications, benefits, and challenges in the educational context. Moreover, it highlights the ethical considerations  and  future  implications  of  AI-based  learning  systems.  Overall,  AI  has extremely significance not only in student life but also in every situation to learn many challenges of anything.